2020
DOI: 10.2196/20182
|View full text |Cite
|
Sign up to set email alerts
|

The United States Medical Licensing Examination Step 1 Is Changing—US Medical Curricula Should Too

Abstract: In recent years, US medical students have been increasingly absent from medical school classrooms. They do so to maximize their competitiveness for a good residency program, by achieving high scores on the United States Medical Licensing Examination (USMLE) Step 1. As a US medical student, I know that most of these class-skipping students are utilizing external learning resources, which are perceived to be more efficient than traditional lectures. Now that the USMLE Step 1 is adopting a pass/fail grading syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…While the mention of international opportunities was scarce, the low percentage of fellowship match lists was particularly concerning, given that over 90% of residents choose to complete an orthopedic surgery fellowship following graduation [ 22 ]. We also found that, despite the anticipated changes to application metrics, including scoring changes to USMLE Step 1, only 28.0% (53/189) of websites mentioned USMLE Step 2 application requirements and 14.3% (27/189) indicated preferences for an eSLOR [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…While the mention of international opportunities was scarce, the low percentage of fellowship match lists was particularly concerning, given that over 90% of residents choose to complete an orthopedic surgery fellowship following graduation [ 22 ]. We also found that, despite the anticipated changes to application metrics, including scoring changes to USMLE Step 1, only 28.0% (53/189) of websites mentioned USMLE Step 2 application requirements and 14.3% (27/189) indicated preferences for an eSLOR [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…Now, the digital age has generated new tools to support this mastery such as online interactive platforms [ 1 - 3 ]. Tools and resources that embrace spaced repetition and retrieval-based practice have demonstrated considerable effectiveness and use in all disciplines [ 4 7 ]. Spaced repetition derives from the spacing effect coined in Hermann Ebbinghaus’s book, Memory: A Contribution to Experimental Psychology , in which he found that continuous repetition spaced in time produces stronger memories [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Acknowledging that it is not possible to memorize everything in Medicine, and the presence of other attractable learning resources (the United States Medical Licensing Examination [USMLE]) might be plausible to absenteeism. However, USMLE's recent pass/fail adoption may positively influence traditional lecture attendance [5].…”
Section: Introductionmentioning
confidence: 99%